2011
DOI: 10.1002/for.1208
|View full text |Cite
|
Sign up to set email alerts
|

Are more data always better for factor analysis? Results for the euro area, the six largest euro area countries and the UK

Abstract: 4Non-technical summary 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 30 publications
0
27
0
2
Order By: Relevance
“…Caggiano et al (2011) showed that using smaller subsets of the available large data set improves the forecast performance of factor models for the six largest Euro Area economies, the Euro Area aggregate and UK. Using Monte Carlo analyses, Alvarez et al (2012) show that small scale factor models outperform larger ones in terms of forecast precision.…”
Section: Selection Of Targeted Predictorsmentioning
confidence: 99%
“…Caggiano et al (2011) showed that using smaller subsets of the available large data set improves the forecast performance of factor models for the six largest Euro Area economies, the Euro Area aggregate and UK. Using Monte Carlo analyses, Alvarez et al (2012) show that small scale factor models outperform larger ones in terms of forecast precision.…”
Section: Selection Of Targeted Predictorsmentioning
confidence: 99%
“…In the literature, alternative techniques and methods have been introduced to perform this information reduction: targeting indicators with thresholding rules (Bai and Ng, 2008, Schumacher, 2010, Bulligan et al, 2012, and Kim and Swanson, 2013, estimating weighted principal components and preselecting indicators with rules that eliminate irrelevant information Ng, 2006, andCaggiano et al, 2011), estimating factors under a sparse prior (e.g. Kaufmann and Schumacher, 2013), and selecting one "representative" indicator of each category in which the large panel can be classified (Alvarez et al, 2012).…”
Section: -The State Of the Art In Short Run Modelling For Gdp Forecasmentioning
confidence: 99%
“…These options, together with the choice of the balancing strategy discussed above (shifting, autoregressive and other specialised algorithms) brings to alternative FM of which much of the literature has supported the usefulness in forecasting euro area GDP; see e.g. Marcellino et al (2003), Rünstler et al (2009), Angelini et al (2011). documented the advantage over simple benchmarks of forecasting euro area GDP with the PFM approach (see Caggiano et al, 2011;Bulligan et al, 2012 …”
Section: Indicators' Selectionmentioning
confidence: 99%
“…One of the issues is how to determine the optimal number of factors in the model; see, for example, Ng (2002, 2007). Another issue of debate is the determination of the optimal size of the database for the extraction of the factors; see, for example, the discussions in Caggiano et al (2011) andden Reijer (2013). A related issue that has attracted relatively little attention in the literature is the gain in forecast accuracy resulting from including autoregressive terms of the target variable in the model specification, i.e.…”
Section: Introductionmentioning
confidence: 99%